Visitors Support for Komodo Dragon Conservation Fund - Mahmud, Arief; Iswandono, Elisa; Chrismiawati, Marliana; Awang, Alvanixon Lamba (Department of Forest Resources Conservation and Ecotourism - IPB University, 2024)
The designation of Komodo National Park as one of the New 7 Wonders in 2012 sparked increased tourism, resulting in growth in Labuan Bajo's hospitality sector, with low entry fees and stakeholders advocating for Komodo dragon conservation. Determining an appropriate entrance fee is crucial for park maintenance and Komodo dragon conservation. This study aims to analyze tourism trends, willingness to pay (WTP) for entrance fees, and willingness to contribute (WTC) to conservation funds. The analysis reveals a consistent rise in visitor numbers from 2015 to 2019, along with significant growth in non-tax revenue, hotel accommodation, and bed capacity from 2010 to 2019. Tourists exhibit strong support for Komodo conservation with a notable USD 25.573 in WTP for domestic visitors and 39.4 for foreign tourists. Respondents express readiness to contribute to conservation funds. Government agencies, local communities, and non-governmental organizations (NGOs) are favored to manage the conservation fund. The preservation of Komodo dragons has a positive impact on ecosystem balance and economic improvement from tourism.